Expressions of Ionianness in the Roman period - Hallmannsecker, M (2020)
The present thesis provides an analysis of expressions of a distinct sense of an Ionian identity (‘Ionianness’) in the Roman period. With the creation of the Roman province of Asia and the ever-increasing degree of incorporation of the Greeks into the Roman Empire, questions of identity gained new relevance and urgency for the Greek provincials. The Ionian cities are thereby a special case, as they, unlike many other cities in Asia Minor, were all old Greek poleis and could look back on a renowned tradition of great antiquity. They also continued to hold common meetings and festivals as members of the Ionian Koinon, which can still be seen as the main focal point of Ionianness in the Roman period. My aim is to complement studies of the extant literary sources – which have traditionally received the greatest share of attention – with analyses of the rich epigraphic and numismatic material from the Ionian cities, which are among the best-attested from the province of Asia. In doing so, I want to achieve a more holistic and nuanced picture, and I hope to contribute to further the understanding of Greek culture under the Roman Empire. The individual chapters are of thematic nature and focus on one aspect of Ionian identity respectively: the perception of Ionia as a cultural region, the Ionian Koinon, myths and cults, ways of time reckoning, and onomastics. The thesis is rounded off by an examination of expressions of Ionianness outside of Ionia, further highlighting its continuing value as a form of cultural capital in the Roman period.